The Implementation of the Discovery Learning Model Assisted by Pansmaperling Media to Improve Students IPAS Process Skills - Sajidda Andani Rahmawati; Siti Masfuah; Lovika Ardana Riswari (STKIP Taman Siswa Bima, 2025)
The teachers' lack of knowledge regarding learning models and media makes students less active in learning. Students' lack of focus in following the lesson due to talking with their friends results in poor learning outcomes, especially in science and science process skills. This type of research is quantitative pre-experimental with a one-group pretest-posttest design. The subjects in this study were 28 fifth-grade students at SD 4 Jekulo. Data collection instruments included test sheets, observation sheets, interview sheets, and documentation. Data analysis techniques used normality tests and hypothesis tests with paired sample t-tests and n-gain tests. The results of the normality test were said to be normally distributed. The paired sample t-test showed a difference in the average results before and after treatment. Science and science process skills learning outcomes were measured using observation sheets at each meeting. There was an increase in science and science process skills learning outcomes in the moderate category. Research using the discovery learning model and pansmaperling media is rarely used because it must be adjusted to the needs and conditions of students. The purpose of this study was to determine the improvement in science and science learning outcomes before and after treatment. Based on this, it can be concluded that the application of the discovery learning model assisted by pansmaperling media can improve science and science process skills learning outcomes.